Principles and Practice of Transplant Infectious Diseases 2019
DOI: 10.1007/978-1-4939-9034-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Cytopenias in Transplant Patients

Abstract: Anemia is commonly seen after solid organ transplant (SOT). It can result from a number of different etiologies including bleeding or hemorrhage, iron deficiency, hemolysis, drug related, lack of erythropoietin, marrow suppression, and congenital etiologies. The frequency and severity of anemia is dependent on the type of solid organ transplant and the duration of time that has passed since the transplant. Much of the data for the causes of anemia following SOT is from renal transplant and cardiac transplant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…With the increasing incidence of NTM infections, it is important to optimize patient tolerability and adherence to therapy [ 16 ]. Evaluating the risks vs benefits of linezolid compared with tedizolid for prolonged durations of therapy, especially in a population possessing baseline risks for cytopenias, will help guide safe antimicrobial therapy [ 17 ]. The purpose of the study was to compare the safety and tolerability of tedizolid and linezolid throughout the treatment course and to describe the microbiological and clinical outcomes of tedizolid- or linezolid-containing regimens for the treatment of NTM in SOT recipients.…”
mentioning
confidence: 99%
“…With the increasing incidence of NTM infections, it is important to optimize patient tolerability and adherence to therapy [ 16 ]. Evaluating the risks vs benefits of linezolid compared with tedizolid for prolonged durations of therapy, especially in a population possessing baseline risks for cytopenias, will help guide safe antimicrobial therapy [ 17 ]. The purpose of the study was to compare the safety and tolerability of tedizolid and linezolid throughout the treatment course and to describe the microbiological and clinical outcomes of tedizolid- or linezolid-containing regimens for the treatment of NTM in SOT recipients.…”
mentioning
confidence: 99%
“…Cytopenia, including leukopenia, anemia, and thrombocytopenia, occurs after a solid organ transplant. The etiology of cytopenia is multifactorial and includes drugs, infections, and post-transplant lymphoproliferative disorders [27]. It also increases the risk of developing further complications, such as opportunistic infections, and may contribute to poor prognosis in patients undergoing LTX.…”
Section: Discussionmentioning
confidence: 99%
“…This raises concern about their ability to mount an effective immune response to COVID 19 vaccination. And therefore warrant the investigation of the impact of both leukopenia and drugs on the immunogenicity of Covid19 vaccine among LTR (8)(9)(10). Finally, studies have shown that comorbidities such as diabetes, hypertension, or heart disease may have a reduced immune response to the vaccine compared to those without underlying health conditions, but this still needs to be demonstrated in the setting of .…”
Section: Introductionmentioning
confidence: 99%